MgCO₃ contents of the fibrous dolomite crystals in methane seep carbonates from Marmorito, northwest Italy - Lu, Yang; Paulmann, Carsten; Mihailova, Boriana; Malcherek, Thomas; Birgel, Daniel; López Correa, Matthias; Lin, Zhiyong; Lu, Liuyi; Milker, Yvonne; Peckmann, Jörn (In: Lu, Y et al. (2023): MgCO₃ contents, structure, and carbon and oxygen isotope compositions of fibrous crystals in a Miocene methane seep carbonate [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.963595, 2023)
Samples were made into thin sections with polished surface. Each spectrum was measure by 10 loops with each one collected for 15 seconds.
Keywords: carbonate cement; Fibrous dolomite; methane seep; Miocene; SD-AOM